Genomic and Functional Characterization of qnr-Encoding Plasmids from Municipal Wastewater Biosolid Klebsiella pneumoniae Isolates - Kaplan, Ella; Sela, Noa; Doron-Faigenboim, Adi; Navon-Venezia, Shiri; Jurkevitch, Edouard; Cytryn, Eddie (Frontiers in Microbiology, 2015)
Municipal wastewater treatment facilities are considered to be “hotspots” for antibiotic resistance since they conjoin high densities of environmental and fecal bacteria with selective pressure in the form of sub-therapeutic concentrations of antibiotics. Discharged effluents and biosolids from these facilities can disseminate antibiotic resistant genes to terrestrial and aquatic environments, potentially contributing to the increasing global trend in antibiotic resistance. This phenomenon is especially pertinent when resistance genes are associated with mobile genetic elements such as conjugative plasmids, which can be transferred between bacterial phyla. Fluoroquinolones are among the most abundant antibiotic compounds detected in wastewater treatment facilities, especially in biosolids, where due to their hydrophobic properties they accumulate to concentrations that may exceed 40 mg/L. Although fluoroquinolone resistance is traditionally associated with mutations in the gyrA/topoisomerase IV genes, there is increasing evidence of plasmid-mediated quinolone resistance, which is primarily encoded on qnr genes. In this study, we sequenced seven qnr-harboring plasmids from a diverse collection of Klebsiella strains, isolated from dewatered biosolids from a large wastewater treatment facility in Israel. One of the plasmids, termed pKPSH-11XL was a large (185.4 kbp), multi-drug resistance, IncF-type plasmid that harbored qnrB and 10 additional antibiotic resistance genes that conferred resistance to 5 different antibiotic families. It was highly similar to the pKPN3-like plasmid family that has been detected in multidrug resistant clinical Klebsiella isolates. In contrast, the six additional plasmids were much smaller (7-9Kbp) and harbored a qnrS -type gene. These plasmids were highly similar to each other and closely resembled pGNB2, a plasmid isolated from a German wastewater treatment facility. Comparative genome analyses of pKPSH-11XL and other pKPN3-like plasmids concomitant to phylogenetic analysis of housekeeping genes from host Klebsiella strains, revealed that these plasmids are limited to a predominantly human-associated sub-clade of Klebsiella, suggesting that their host range is very narrow. Conversely, the pGNB2-like plasmids had a much broader host range and appeared to be associated with Klebsiella residing in natural environments. This study suggests that: (A) qnrB-harboring multidrug-resistant pKPN3-like plasmids can endure the rigorous wastewater treatment process and may therefore be disseminated to downstream environments; and (B) that small qnrS-harboring.